Nitrogen and phosphorus requirements for the growth and nodulation of Cajanus cajan in Panamanian soils - Hernández, B.C.; Méndez Lay, J.M.; Focht, D.D. (International Center for Tropical Agriculture, 1982)
Chemical analysis and missing element trials with Sorghum vulgare L. showed that three Panamanian soils, representative of three great soil groups, were deficient in both nitrogen (N) and phosphorus (P). When a greenhouse trial was undertaken to test the response of Cajanus cajan to rhizobial inoculation, N and P fertilization in these soils, no response was obtained in either the Río Hato or Los Santos soils. There was a definite response to P and a slight response to inoculation in the Pacora soil, which had the poorest fertility level. N applications depressed nodulation. The lack of response of Cajanus cajan to P in the Río Hato soil was attributed to the high incidence (55 percent) of VA mycorrhizal infection. Inoculation of Cajanus cajan with both Rhizobium and Glomus may be important in low-fertility soils.